2012
DOI: 10.1155/2012/218429
|View full text |Cite
|
Sign up to set email alerts
|

A 3 DOF Model for an Electromagnetic Air Mount

Abstract: A 4 × 4 matrix model with three degrees of freedom is proposed as a means for controlling microvibrations and applied to an electromagnetic isolator. The model was derived from an assumption based on small-and low-frequency vibrations. The coordinates of the 3 DOF was composed of the 4 variables, representing a vertical position, pitch, roll, and a proof term. The coordinates were calculated from the 4 position sensors in the isolator and formulated into a 4 × 4 matrix, which possesses inversive full rank. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…And then they built an EMASVI model with 3 degrees of freedom, including a vertical displacement, an inclination angle, and a rotating angle and carried out a shock experiment. 7 The result of experiment indicated that stabilization time of this model reduced to 25% compared to that of the model with 1 degree of freedom. Electromagnetic actuator was installed around air spring in another paper about EMASVI.…”
Section: Introductionmentioning
confidence: 84%
“…And then they built an EMASVI model with 3 degrees of freedom, including a vertical displacement, an inclination angle, and a rotating angle and carried out a shock experiment. 7 The result of experiment indicated that stabilization time of this model reduced to 25% compared to that of the model with 1 degree of freedom. Electromagnetic actuator was installed around air spring in another paper about EMASVI.…”
Section: Introductionmentioning
confidence: 84%
“…Nonetheless, it is not sufficient to generate a control force to reduce the unwanted vibrations that occur in large-sized precision manufacturing machines with high-speed motion. Another potential candidate for vibration control of plane motions in precision manufacturing machinery is the use of electromagnetics (EM) actuators, which can have several configurations such as serial connection [8]. However, it is very difficult to satisfy the vibration criteria using piezoelectric or EM actuators because these actuators cannot generate sufficient power for controlling large magnitudes of the vibration, even though their response to the external input is fast.…”
Section: Introductionmentioning
confidence: 99%
“…The air mount must satisfy the vibration criteria of the floor vibration, and should also absorb the machine vibration quickly. We have been developing air mounts based on pneumatic and EM forces for precision machines in clean rooms [12,13]. The air mount is a kind of active air spring in which EM actuators are present within a pneumatic system.…”
Section: Introductionmentioning
confidence: 99%